Efek Dialectical Behavior Therapy (DBT) Terhadap Pasien Dengan Perilaku Kekerasan - Sri Dewi Musa; Basmalah Harun (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction violent behavior is a situation where a person can harm himself and others both physically and psychologically. To reduce violent behavior, it is necessary to do prevention that applies Dialectical Behavior Therapy (DBT) therapy. Dialectical Behavior Therapy (DBT) is a psychotherapeutic therapy intervention that can assist patients in controlling emotions, accepting the present state, and changing negative behaviors that previous patients have in the direction of more positive behaviors. Purpose Learn how dialectical behavior therapy (DBT) affects patients with violent behavior. Methods using this literature study are by searching through electronic databases, Garuda, and Google Scholar. The inclusion criteria used are articles in 2011-2021 and resulted in 3 significant research articles. Results show dialectical behavior therapy (DBT) is very effectively used as an intervention to help patients with violent behavior. Conclusion the effects of dialectical behavior therapy (DBT) are effective in patients in controlling their negative emotions.